The Implications of Good Governance of Village Government Office in Sidoarjo - Rita Ambarwati; Affandy Winarko Mudjib; Fita Fitria Lestariana; Gogor Arif Handiwibowo (Binus Business Review, 2019)
This research examined determinant factors of good governance of a village government office in Sidoarjo. This research used a survey and a cross-section through a questionnaire as the data collection. The unit of analysis was the citizen who worked as a state civil apparatus and had used public services in a village government office. To determine the sample, the researchers used a simple random sampling. The data were analyzed using Structural Equation Modeling (SEM). The results show that the rule of law and responsiveness are dominant indicators to form good governance. However, transparency and good commitment are less dominant indicators in forming good governance. The practical implications of this research are useful for the local government as they need to increase the role of good governance in improving public service performance, especially for village service.